Konstruksi Sistem Jaminan Sosial Nasional Bidang Kesehatan - Yusriando Yusriando (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2019)
The purpose of this paper is to understand and analyze the current National Social Security System Construction in the Field of Health. The research paradigm used is the constructive paradigm. The research specification is descriptive analytical. Methods of socio legal research approach. Primary and secondary data type data. Data Collection Techniques with Literature Study, Observation, and Interview with descriptive qualitative data analysis with inductive methods. Research and Discussion Results, that the Construction of the National Social Security Program in the Field of Health at present are: Puskesmas functioned to carry out promotive, preventive efforts, without neglecting curative and rehabilitative efforts in their working area. After collaborating with BPJS as FKTP I, most of them are directed towards providing curative and rehabilitative efforts by not ignoring promotive and preventive efforts. In practice FKTP I does not yet have the ability to handle 155 types of diseases as required, both in terms of human resources and health infrastructure, but even though FKTP I has not been able to carry out its obligations optimally.Keywords: System, National Social Security, Health.